The threadsnake tangle: lack of genetic divergence in Epictia tenella (Squamata, Leptotyphlopidae): evidence for introductions or recent rafting to the West Indies. (1st September 2016) - Murphy, John C.; Rutherford, Mike G.; Jowers, Michael J.
ABSTRACT: The confusion between the Neotropical threadsnakes Epictia albifrons (Wagler) and Epictia tenella (Klauber) has been ongoing for decades. The lost holotype of Stenostoma albifrons, a poorly detailed original description, and dubious type locality confound the problem. Recently an extant series of nine museum specimen from Belém, state of Pará, Brazil were selected as topotypes for Epictia albifrons Wagler. From this series a neotype was designated. Here we compare the morphology of the neotype to specimens from Trinidad and Guyana, confirming that they are Epictia tenella (Klauber) not E. albifrons (Wagler). We also compare four mitochondrial and one nuclear marker from Trinidad and mainland (Guyana) Epictia tenella populations and find E. tenella relatively widespread with minimal genetic diversification between island and mainland specimens. Hypotheses that may explain the low divergence for this small, fossorial snake are explored and discussed: over-water rafting, human-mediated dispersal, and avian-mediated dispersal.